Tort law (concept) - Papayannis, Diego M. (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
In this brief essay I present a view of tort law as a form of interpersonal responsibility. First, I attempt to provide a characterization of the practice, identifying the problem addressed by tort law, explaining how it differs from other forms of liability and describing the way it typically works. Then, I focus on its structure, in order to analyze the norms that are distinctive of the practice and examine how they relate to each other and to other norms that, without being distinctive, are necessary for its operation.